X-ray Diffraction and Mineralogical Study of Coastal Soils and Sediments - Sonawane, D.S.; Shrivastava, V.S. (Asian Journal of Chemistry, 2016)
Clay minerals containing soil samples were collected from Mumbai and Surat. The samples were precipitated and concentrated by centrifuge method for the extraction of clay. X-ray diffraction (XRD) and scan electron microscopy (SEM) analyses were carried out for these samples. The investigation indicates that the clay samples contain quartz, kaolinite, illite and little amount of smectite minerals. Beside the above analyses the physico-chemical parameters of the soil samples have also been evaluated.